Impact Assessment of Hailstorm on Khasi mandarin and other Horticultural Crops in Umiam, Meghalaya - Rymbai, H.; Deshmukh, N.A.; Verma, V.K.; Talang, H.D.; Devi., M.B.; Jha, A.K. (Indian Journal of Hill Farming, 2019)
Hailstorm is frequently occurs in Meghalaya and caused crops damage and losses including houses. In Umiam areas, it was observed on 03rd, 16th and 17th April, 2018 which affected horticultural crops particularly Khasi mandarin at varying degrees. The incident has reduced the commercial and appealing value of the crops. So far meagre information is available on impact of hail damage on horticultural crops. Therefore, the main objective of this study was conducted to monitor the impact of hail storm on Khasi mandarin and other horticultural crops. Result showed significant damaged in all the crops at varying degree; however, the severity of damage was higher at flowering, fruit setting, fruiting stage, and nursery stage. In Khasi mandarin, the damage for leaves was recorded (8.33%), flowers (46.66%) and fruits (42.76%), while flower drop (62.66%) and fruit drop (53.67%) was observed. In peach, hailstorm causing 61.3% damage to matured fruit, 22.5% fruit drop and 32.0% leaf damaged. In all the ornamental flower crops, the damage is measured in term of damaged stalk and broken shoot tip. In gerbera, damage occurrence was recorded 86.66% in leaves and flowers, 92.33%. In gladiolus, the damage was recorded 13.66% in leaves and 96.66% in flowers. In dolichos bean, flower drops (pole type, 53.54-61.48%; bush type, 55.86-57.69%) and fruit drop (pole type, 17.53-23.68%; bush type, 59.09- 66.67%). In tomato, flower drop (31.25- 89.41%) and fruit drop (14.29-31.43%) was recorded. The flower and fruit drops in vegetables may lead to 35-58% yield loss in dolichos bean and 30-45% in tomato due to hailstorm. The tender seedlings of Khasi mandarin at two leaf stage were highly damaged (93.33%) leading to its drying and dying. Result show that it is the need of the hour to develop pre-event measures post hail storm strategies to minimize crop losses.